The Implementation of the Good Faith Principle in Unbalanced Banking Credit Agreements Based on Substantive Justice - Sryani Br. Ginting; Christina N.M. Tobing (Global Legal Review, 2026)
Contracts as legal instruments, play a vital role in business activities, which can be viewed not only from a normative aspect but also through philosophical and economic dimensions. Ideally, the formation of contractual relationships is based on fundamental principles to ensure the realization of fairness and equity for all parties involved. One of the primary principles determining the quality of justice in a contract is good faith, which serves as a guideline for the interpretation and execution of agreements. This research aims to analyze the regulation of good faith in national contract law, examine its application in bank credit agreements which often exhibit an imbalance in the parties' positions and formulate a regulatory model oriented toward substantive justice. The research method employed is normative legal research. The approaches used include statutory, conceptual, and case-based approaches. The results indicate that the principle of good faith in Indonesian contract law (the Civil Code) possesses both juridical and philosophical meanings aligned with John Rawls’ theory of justice and the values of Pancasila. Good faith must be interpreted by judges in their rulings in concreto and systematically to ensure clarity of meaning through "judge-made law." This aligns with positivist schools of thought and the teachings of sociological jurisprudence. In judicial practice, judges tend to apply the principle of good faith contextually, particularly in resolving disputes involving imbalanced contracts, by considering the sense of justice, propriety, and the social conditions of the parties. Furthermore, judges play an active role in legal discovery (rechtsvinding) through progressive interpretation. Legal interpretation by judges may utilize legal hermeneutics that an incisive, profound, and holistic method of interpretation within the framework of unity between the text and its context. This research recommends the strengthening of normative regulations regarding good faith, specifically in bank credit agreements, as well as consistency in its application through jurisprudence and judicial guidelines to avoid disparity in court rulings.